The Effect of Non-financial Performance Measurement System on Firm Performance - Ahmad, Kamilah; Zabri, Shafie Mohamed (International Journal of Economics and Financial Issues, 2016)
Non-financial performance measurement systems have emerged as a results of the growing use of modern manufacturing practices where it is able to improve crucial activities for performance improvement. This research examines the effect of the NFPMSs on firm performance within Malaysian manufacturing firms using a survey questionnaire. Based on 118 useable questionnaires, the results demonstrate that there are high extent of use of NFPMSs related to internal efficiency, product development & growth and corporate social responsibility. Furthermore the data provide support as to the effect of NFPMSs on firm performance within a manufacturing environment. Therefore the finding ascertains that NFPMSs play significant roles in the production and operations environment especially for increasing the performance of the firm. Keywords: Non-financial performance measurement, manufacturing firms, performance JEL Classifications: M1; M11